SISTEM INFORMASI GEOGRAFIS PEMETAAN TEMPAT PEMBUANGAN SEMENTARA - Ricki Gozal; Dedi Trisnawarman (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
Geographic Information System (GIS) is a computer based system used to storing and manipulating geographic information. GIS can also merge data, manage data, and analyze data and produce an output to support a decision making.The purpose of this thesis is to make a GIS application that maps a location of each temporary dumpsite in Jakarta. The development of this GIS is using System Development Life Cycle (SDLC) method includes of Planning, Analyze, Design, and Implementation. This GIS will using ArcGIS program to make a map of the temporary dumpsite's location. The output would be showed with map of temporary dumpsite distribution with ArcGIS, and the output will embedded to a website.